The Effect of Alcoholic Extract of Anabasis syriaca Iljin on Biochemical and Histological Parameters in Rats - Suad M. Kloub; Saleem A. Banihani; Omar M. Atrooz; Wael M. Hananeh (Journal of Toxicology)
This work investigates the effect of the alcoholic extract of Anabasis syriaca Iljin on biochemical and histological parameters in male rats. The lethal dose (50% of the plant extract) was assessed, and three separate doses (1/10th, 1/15th, and 1/20th) were orally gavaged for two weeks into three study groups of animals (five rats in each group), with one group used as a control and gavaged normal saline via the same route. Blood was collected after overnight fasting, and 24 biochemical parameters were evaluated. The gross and microscopic findings were reported after the collection of specimens from the animals and processed routinely for standard histological procedures. Among all tested biochemical parameters, a significant increase was noted in fasting serum glucose (p≤0.010), troponin (p≤0.001), and creatine kinase (p≤0.001), while a significant decrease was found in triglycerides (p≤0.001) and low-density lipoprotein (p=0.001). On the other hand, no significant histopathological lesions were present within the examined tissues of all groups. In conclusion, ethanolic extract of Anabasis syriaca negatively affected the cardiac function of male rats and increased their serum glucose but reduced their serum triglycerides and low-density lipoprotein.